Ketidakadilan dalam Praktik Penjualan Kakao: Perspektif Hukum Islam - Zul Azimi (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to determine the practice of selling cocoa and the views of Islamic law on selling cocoa in Trienggadeng District. The research method used in this research is qualitative research with direct data collection in the field. The research results show that the practice of buying and selling cocoa in the Trienggadeng District is strongly influenced by local processes and existing regulations. Even though there are obstacles and variations in price and quality, the local cocoa market remains an important part of the economy and sustainability of cocoa farmers in Trienggadeng District. In the practice of buying and selling cocoa in Trienggadeng District, Pidie Jaya Regency, there are violations of the principles of Islamic business ethics, such as balance, fairness, and honesty. Mixing the quality of cocoa by farmers and buyers not only violates the values of Islamic morality, but also goes against the prohibitions in Islamic business, such as tadlis, gharar, ghishy, and khalabah. This shows the need for awareness and commitment to running a business by Islamic teachings which emphasize the importance of truth, justice, and honesty.